Optical, thermal, strength properties and SHG efficiency of KDP single crystals doped with N,N'-dimethyl urea - Kostenyukova, E.I.; Bezkrovnaya, O.N.; Dolzhenkova, E.F.; Pritula, I.M.; Doroshenko, A.G.; Chaika, M.A.; Fedorov, A.G.; Khimchenko, S.V. (Functional Materials, 2018)
Pure single crystals of potassium dihydrophosphate (KDP) and the ones doped with N,N′-dimethylurea (NN′DU) were grown by the temperature reduction method onto a point seed. The dopant concentration in the mother liquor was 0.15 and 0.45 wt. %. The study of the transmission spectra of KDP:NN′DU crystals, as well as the change in their strength properties (mechanical and laser strength) and thermal properties (differential thermal and thermogravimetric analyses) in the growth sectors {101} and {100} confirms the occurrence of NN′DU molecules in both growth sector. It was shown that doping of the crystals with NN′DU molecules led to an increase in the efficiency of second harmonic generation by two times in the sector {100} of KDP:NN′DU crystals as compared with pure KDP.